The LSTA's complete credit agreement guide - Bellucci, Michael J.; McCluskey, Jerome (McGraw-Hill Education, 2017)
The definitive guide for navigating today's credit agreements Today's syndicated loan market and underlying credit agreements are far more complex than ever. Since the global financial crisis, the art of corporate loan syndications, loan trading, and investing in this asset class have changed dramatically. Lenders are more diverse, borrowers more demanding, and regulations more stringent. Consequently, the credit agreement has evolved, incorporating many new provisions and a host of revisions to existing ones. The LSTA's Complete Credit Agreement Guide brings you up to speed on today's credit agreements and helps you navigate these complex instruments. This comprehensive guide has been fully updated to address seven years of major change-which has all but transformed the loan market as we knew it. It provides everything you need to address these new developments, including what to look for in large sponsor-driven deals, the rise of "covenant lite" agreements for corporate borrowers seeking fewer covenant restrictions, Yankee Loans, other products resulting from globalization, and other product developments driven by the diversification of the investor class. You'll benefit from the authors' in-depth coverage of all the nuances of today's credit agreements, as well as their tips on how to protect your loan, manage defaults, and navigate cross-border deals. This reliable guide covers: o Commitments, Loans, and Letters of Credit o Interest and Fees o Amortization and Maturity o Conditions Precedent o Representations o Covenants o Guarantees and Security o Defaults and Enforcement o Interlender, Voting, and Agency issues o Defaulting Lenders o Assignments, Participations, and Disqualified Lender ListsBorrower Rights o Regulatory Developments Structuring and managing credit agreements has always been a difficult process - but now it's more complicated than ever. Whether you work for a company that borrows money in the syndicated loan market or for a bank, a hedge fund, pension fund, insurance company, or other financial institution, the LSTA's Complete Credit Agreement Guide puts you ahead of the curve of today's credit landscape. --Provided by publisher
Includes index. - Includes bibliographical references and index. - Print version record and CIP data provided by publisher
Keywords: Credit; Crédit; credit